Importance of Heat Insulation for Creating Energy Efficiency in Current Buildings: Bursa, Nilüfer/Turkey Example - Senkal Sezer, Filiz (European Journal of Sustainable Development, 2017)
The majority of the current building stock in Turkey is composed of buildings that are not insulated. One of the most important items of the agenda is insulating these buildings in time to use energy efficiently (to create energy efficiency). Due to the increase of residential energy consumption related to heating and cooling, suggestions to speed up the transformation of uninsulated buildings to insulating buildings are needed. Similar to the rest of the world “Measures to Increase Energy Efficiency of Buildings” are among the future goals of administrational policies. Taking into consideration all the research in this area the residential Ataevler Quarter in the Nilufer district of the city of Bursa - the 4th largest city in Turkey - was selected for the analysis in the scope of this paper. There are a total of 2891 apartments in the research area, which is composed of 16 building complexes and 254 building blocks. The research will first analyze the current situation of the residential area. After the initial analyses CO2 emissions (tons), heating energy need (kWh/m2) and heat loss amount (kWh) that will have acquired after insulating uninsulated buildings will be presented. The analyses have shown that insulating walls and roofs of the current buildings will reduce CO2 emissions and fuel consumption almost by 30%. The contribution of this savings to the national economy, budget of the users, and protection of the buildings and the environment is significant. It is believed that the data should be presented to and evaluated by relevant parties in order to contribute to the development of future strategies that aim to reduce energy consumption of current buildings to the minimum. Keywords: Energy efficiency, heat insulation, insulation of buildings